(untitled) - Fletcher III, William Miles (London, 1989)
Miles Fletcher examines the role of the Japanese business community in helping the nation solve an unprecedented combination of economic challenges in the 1920s and 1930s: chronic trade deficits, world depression, rampant protectionism, and mobilization for war in Asia. Because of such severe crises, business executives changed their attitudes toward foreign trade and types of national economic policies needed to succeed in a global marketplace
Keywords: Japan,Japan,Nhật Bản,Nhật Bản; Commercial policy,Economic conditions,Chính sách thương mại,Điều kiện kinh tế